Extensive Ameloblastoma of the Mandible - Chowdhury, Md Obaidur R; Islam, Saiful; Chowdhury, WR; Haque, ME (TAJ: Journal of Teachers Association, 2009)
The ameloblastoma is the most common and aggressive odontogenic tumour of the jaws. But only rarely the anterior portions of the jaws are involved. Since extensive ameloblastoma of the mandible crossing the symphysis upto the canine region of the opposite site is a rare occurrence, so we are encouraged to present this case for academic interest. doi: 10.3329/taj.v15i2.3918 TAJ December 2002; Vol.15(2): 93-95